2015
DOI: 10.1007/s00068-015-0514-z
|View full text |Cite
|
Sign up to set email alerts
|

Blunt abdominal trauma and mesenteric avulsion: a systematic review

Abstract: Mesenteric avulsion is rare and has a complex and vague presentation. Due to its potential mortality and morbidity, emergency physicians should keep a high index of suspicion in individuals with blunt abdominal trauma from any mechanism of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…3) in blunt abdominal trauma often occur in high-speed vehicle accidents frequently due to seatbelt restraints [50•]. A retrospective report by Frick et al [51] showed that 29.7% of mesenteric lacerations lead to bowel devascularization (Fig.…”
Section: For Whom?mentioning
confidence: 99%
“…3) in blunt abdominal trauma often occur in high-speed vehicle accidents frequently due to seatbelt restraints [50•]. A retrospective report by Frick et al [51] showed that 29.7% of mesenteric lacerations lead to bowel devascularization (Fig.…”
Section: For Whom?mentioning
confidence: 99%
“…16 Study conducted on 182 cases of peptic ulcer perforations (150 duodenal, 32 gastric) by Fong found that the intraabdominal abscess (22 cases), wound infection (26 cases) and generalized bacterial peritonitis (18 cases) were most common complications. 12,13,17 Our study reveals that the average duration of stay in hospital was nearly same for all cases of gastrointestinal perforation (16.52-18.5 days) so we can conclude that stay in hospital was independent of the cause of gastrointestinal perforation. Average duration stay in hospital was less in patients who were managed conservatively it may be due to their general condition were good and having fewer complications.…”
Section: Discussionmentioning
confidence: 63%
“…Upon considering similar mechanisms of mesenteric laceration, Heimlich maneuver for choking, rope wounds across the waist in the game of "tug of war", and seatbelt injuries are reported as possible culprits of mesenteric injury [5,9,10]. The common point of these traumas including our case to cause mesenteric laceration is a rapid elevation of the intra-abdominal pressure conveyed to the stalk of the mesentery.…”
Section: Discussionmentioning
confidence: 72%
“…After removal of a fist-sized hematoma and a large amount of intraabdominal hemorrhage, approximately 5 cm in length of a mesenteric laceration in the transverse colon adjacent to the left side of Treitz's ligament was revealed. Hemostasis was achieved by suture ligations but repair of the laceration was impossible because the tissue was too fragile mesenteric laceration is very rare and theoretically seldom happens because external forces need to be conveyed directly to the mesentery in the abdominal trauma cases [5].…”
Section: Discussionmentioning
confidence: 99%